Preparation and Distribution of Cannabis and Cannabis-Derived Dosage Formulations for Investigational and Therapeutic Use in the United States - Thomas, Brian F.; Pollard, Gerald T. (Frontiers in Pharmacology, 2016)
Cannabis is classified as a schedule I controlled substance by the US Drug Enforcement Agency, meaning that it has no medicinal value. Production is legally restricted to a single supplier at the University of Mississippi, and distribution to researchers is tightly controlled. However, a majority of the population is estimated to believe that cannabis has legitimate medical or recreational value, numerous states have legalized or decriminalized possession to some degree, and the federal government does not strictly enforce its law and is considering rescheduling. The explosive increase in open sale and use of herbal cannabis and its products has occurred with widely variable and in many cases grossly inadequate quality control at all levels—growing, processing, storage, distribution, and use. This paper discusses elements of the analytical and regulatory system that need to be put in place to ensure standardization for the researcher and to reduce the hazards of contamination, overdosing and underdosing for the end-user.